Diseases and Pest of Anthurium and Orchids - P. Sivaprasad; K.S. Meenakumari (Ludhiana Kalyani, 2011)
This book has been felt by the authors through numeres enquires raised by cultivators and interested researchers.
Symptems of Plant Diseases Diseases of Anthurium Pest of Orchids
Keywords: Symptems of Plant Diseases; Diseases of Anthurium; Pest of Orchids